Structural behaviour of precast concrete sandwich panel using recycled aggregate concrete under transverse load - Al. Mabrouk Khalifa, Hamza Masaud (2013)
Previous studies have been focusing on finding alternative materials in a composite building system in order to provide a strong, environmental friendly, low cost material to be used in the construction industry. In this research, recycle aggregate, RA, has been used instead of natural aggregate. This study presents the viability of RA with different ratios of 25, 50, 75 and 100% in Recycled Aggregate Concrete Sandwich Panel, RACSP. The structural behavior of the RACSP was investigated experimentally and analysed in the context of transverse load capacity, loaddeflection profile, load strain curves, cracking patterns and mode of failure. LVDT was used to measure the mid-span deflection and the slip between both wythes of RACSP. Strain gauges were used to measure the strain on the surface of concrete wythes. It was found that the strength of the panels with RA decreased nonlinearly with the increase of percentage replacement of RA in concrete. Control Panel with NA showed the highest value of ultimate load in comparison with others. The percentage of reduction in the ultimate load of panels with RA was about 15% for an increase the replacement percentage of RA whereas the maximization in the ultimate load was about 31% in comparison with Control Panel. It was observed that all the slab ultimately failed by tension steel failure. It was noticed that the first crack occurred at about 48-67% of the failure load. Influence of the RA and the impact of transverse load on the ultimate strength of RACSP specimens have been discussed. Cracks were observed in both wythes.